The Effects of Consumption of Cooked Beans (Phaseolus vulgaris) and Serotonin Precursor Diets on Scopolamine-Impaired Memory and Motor Co-ordination in Mice. (Nigerian Journal of Physiological Sciences, 2025)
Alzheimer’s disease (memory impairment disorder) and motor co-ordination disorders are on the increase worldwide. 5-Hydroxytryphamine (serotonin) is involved in short term memory and motor co-ordination (Buhot et al., 2000., Cabaj et al., 2017).  Whether beans that contain serotonin precursor (tryptophan) can ameliorate memory and motor co-ordination impairment has not been previously ascertained. Therefore, this research was to study the effects of consumption of cooked beans (Phaseolus vulgaris) and serotonin precursor diets on scopolamine-impaired memory and motor co-ordination in mice. Sixty mice were randomly assigned into 6 groups (10 mice per group) namely; Control, Scopolamine only, Scopolamine with 50% cooked beans diet, Scopolamine with serotonin precursor diet, 50% cooked beans diet only and serotonin precursor diet only. Preliminary studies on phytochemical analyses were done before learning/memory and motor co-ordination were also studied. Standard methods were used to study learning/memory and motor coordination. The results showed that preliminary phytochemical screening of cooked beans indicated the presence of tryptophan, flavonoids, alkaloids, and polyphenols (antioxidants). Learning was impaired in Scopolamine only group compared to control and other test groups (p